2016
DOI: 10.1186/s12938-016-0265-z
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral artery enlargement predicts carotid plaque progression based on machine learning algorithm models in apoE−/− mice

Abstract: BackgroundThis study specifically focused on anatomical MRI characterization of the low shear stress-induced atherosclerotic plaque in mice. We used machine learning algorithms to analyze multiple correlation factors of plaque to generate predictive models and to find the predictive factor for vulnerable plaque.MethodsBranches of the left carotid artery in apoE−/− and C57BL/6J mice were ligated to produce the partial left carotid artery model. Before surgery, and 7, 14, and 28 days after surgery, in vivo seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…No adverse biological effects were observed from the use of eXIA 160. Li et al [4] used machine learning algorithm models in ApoE−/− mice to predict carotid plaque progression. They found that contralateral carotid artery diameter at 7 days after surgery was the most reliable predictive factor in plaque progression.…”
mentioning
confidence: 99%
“…No adverse biological effects were observed from the use of eXIA 160. Li et al [4] used machine learning algorithm models in ApoE−/− mice to predict carotid plaque progression. They found that contralateral carotid artery diameter at 7 days after surgery was the most reliable predictive factor in plaque progression.…”
mentioning
confidence: 99%